Harriet's hare - King-Smith, Dick.; Roth, Roger (New York : Knopf, 1997)
A young girl's life with her father on their farm in England is changed when she befriends a talking hare that is really a shape-changing alien.
"A Knopf Paperback."
School Library Journal
Child Study Children's Book Committee
Booklist starred
4.8
3-6
Keywords: Extraterrestrial beings -- Fiction; Hares -- Fiction; Farm life -- England -- Fiction; England -- Fiction; Extraterrestrial beings -- Fiction; Farm life -- England -- Fiction; Rabbits -- Fiction; England -- Fiction